2017
DOI: 10.19072/ijet.280499
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Aerodynamics Characteristics of NACA 0015 Aerofoil

Abstract: Abstract-An aerofoil is a streamline body. Symmetric aerofoil (NACA 0015) is used in many applications such as in aircraft submarine fins, rotary and some fixed wings. The ultimate objective of an aerofoil is to obtain the lift necessary to keep an airplane in the air. But construction of the blade with proper angle of attack and implementation has significant effect on lift force. Insufficient lift force might cause fail of airplane flying, especially at high speed. Modern technologists use different simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Furthermore, several authors have shown that, depending on the blades' angle of attack and their shape, the contours of static pressure and the contours of velocity magnitude around the NACA airfoil evolve. 84,85 Depending on its position and angle, these pressure differences along the blade should impact the air flows and damage caused.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several authors have shown that, depending on the blades' angle of attack and their shape, the contours of static pressure and the contours of velocity magnitude around the NACA airfoil evolve. 84,85 Depending on its position and angle, these pressure differences along the blade should impact the air flows and damage caused.…”
Section: Discussionmentioning
confidence: 99%
“…As the current on the airfoils is often close to twodimensional, it is sufficient to examine the flow properties around the flow around a single cross-section as the flow characteristics remain the same in all sections along the airfoil [20]. Airfoil cross-sectional geometry is shown in Fig.…”
Section: Aerodynamic Performance Parameters Of Airfoilsmentioning
confidence: 99%
“…The drag force depends on both the pressure and friction distribution along the surface. Because of the different shapes and dimensions of the airfoils developed for various purposes, dimensionless coefficients are taken into consideration in the comparisons and evaluations [20]. C L eq.…”
Section: Aerodynamic Performance Parameters Of Airfoilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds sayı kaldırma katsayısının artmasıyla biraz artar ve belli bir noktadan sonra azalır. Azaldığı kısımda kanat profili üzerinde büyük negatif basınç oluşmaktadır (Rubel, Uddin, Islam, & Rokunuzzaman, 2016) Rüzgâr tünelinde yapılacak olan deneysel çalışmaların başlangıcı literatürde değerleri bulunan bir kanat profili ile yapılması düşünülmüştür. NACA0015 kanat profili imal edilmesi ve literatür karşılaştırılması bakımından tercih edilmiştir.…”
Section: Introductionunclassified